Ageing characteristics and lifetime model of oil–paper insulation for oil‐immersed paper condenser bushing - Sihang Gao; Lijun Yang; Tingjing Ke (High Voltage, 2021)
Abstract This study extensively investigated the ageing characteristics and lifetime model of oil–paper insulation for oil‐immersed paper condenser bushing. The accelerated thermal and electrothermal ageing experiments of oil‐immersed paper condenser bushing were conducted respectively. The properties of oil–paper insulation during the ageing process were investigated. Results showed that descending speed of degree of polymerization of the innermost and the outermost layer paper was higher than that of middle layer paper, the difference in water content on different paper layers caused varying deterioration speeds. The aluminium foil contributed to a surge in aluminium dissolution in oil, further accelerating the ageing of insulation. Based on the obtained degree of polymerization data under thermal ageing at 90°C, 100°C and 130°C, the lifetime model of oil–paper insulation for condenser bushing model was established. In addition, the surface breakdown of the scale model of bushing occurred after 133 days ageing, the properties of bushing decreased gradually during the ageing process and sharply after the breakdown. Degree of polymerization deviation of different paper layers in bushing between calculated value according to the above lifetime model and actual value of bushing after the breakdown was less than 6%, further verifying the validity of lifetime model.